2004
DOI: 10.3143/geriatrics.41.426
|View full text |Cite
|
Sign up to set email alerts
|

Association between social support and depression in the elderly Japanese population

Abstract: To determine the association between social support and depression in elderly Japanese, we conducted a Comprehensive Geriatric Assessment among residents aged 70 years or over. Out of 2,730 eligible subjects, 1,179 participated in the survey and 1,146 (480 men and 666 women) were analyzed. The Geriatric Depression Scale (GDS) was used to estimate depression status. The subjects were divided into two groups: depressive (GDS>11 or taking antidepressant drugs) and non-depressive (GDS<11). Various levels of social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 0 publications
4
21
0
1
Order By: Relevance
“…Koizumi et al reported that negative responses to the questions “Do you have someone with whom you can consult when you are in trouble?” and “Do you have someone who can take care of you when you are ill in bed?” were significantly associated with an increase in the risk of depression. 23 , 24 The finding is consistent with, and supports, the present results for persons aged 65 years or older. The depressive symptoms detected by the GDS and the psychological distress detected by the K6 reflect common underlying factors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Koizumi et al reported that negative responses to the questions “Do you have someone with whom you can consult when you are in trouble?” and “Do you have someone who can take care of you when you are ill in bed?” were significantly associated with an increase in the risk of depression. 23 , 24 The finding is consistent with, and supports, the present results for persons aged 65 years or older. The depressive symptoms detected by the GDS and the psychological distress detected by the K6 reflect common underlying factors.…”
Section: Discussionsupporting
confidence: 91%
“…Although this is the first large population-based epidemiological study using the K6 in an Asian country, previous studies 23 , 24 have used other mental health scales, such as the Geriatric Depression Scale (GDS) 25 among Japanese populations. Koizumi et al reported that negative responses to the questions “Do you have someone with whom you can consult when you are in trouble?” and “Do you have someone who can take care of you when you are ill in bed?” were significantly associated with an increase in the risk of depression.…”
Section: Discussionmentioning
confidence: 99%
“…These questions were extracted from a previous study regarding social support and elderly depression in a rural community (33). A strong association between negative answers to these items and depression has been confirmed in two Japanese community studies of elderly populations (33,34). A single summed score was calculated based on the PSS 1-5.…”
Section: Assessment Of Other Variablesmentioning
confidence: 84%
“…Older adults with chronic medical conditions [25 -27], physical impairment [25,27,28], or insufficient social support [28,29] are more likely to be depressed, and such characteristics might also affect body weight. Thus, careful consideration of these potential important confounding or effect modifying factors is needed when analyzing the data.…”
Section: Introductionmentioning
confidence: 99%